Pengaruh Risiko Kredit, Risiko Pasar dan Risiko Likuiditas terhadap Profitabilitas Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Kamaluddin, Kamaluddin; Ika, Beatrix Cindy Antia (University of Merdeka Malang, 2023)
This research examines the influence of credit risk (NPL), market risk (beta), and liquidity risk (LDR) variables on bank profitability (ROA). This research uses a quantitative approach with a sample of 20 banks. According to this research, credit risk and market risk contribute to profitability. There is a negative and relevant influence between credit risk (NPL) and market risk (BETA) on profitability (ROA). Banking entities need to minimize credit risk and market risk in order to increase profitability.